Analisis mutu briket arang dari limbah biomassa campuran kulit kopi dan tempurung kelapa dengan perekat tepung tapioka - Bagus Setyawan; Rosiana Ulfa (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2019)
Plantation wastes such as coffee skins and coconut shells in Indonesia have not been utilized optimally. Waste can be utilized for the manufacture of charcoal briquettes as an alternative fuel. The purpose of this study was to determine the quality of charcoal briquettes from biomass waste mixed with coffee skin and coconut shell with tapioca flour adhesive. This research is a type of laboratory experimental research. The study used a Completely Randomized Design (CRD) with 3 replications. Testing the quality of charcoal briquettes includes tests of water content, ash content, combustion rate, and heating value. The research data will be compared with the International charcoal briquette quality standards and the Indonesian National Standard (INS). The results showed that the water content and an ash content of the charcoal briquettes were still below the international charcoal briquette quality standards and INS. However, the heating value of this charcoal briquette is surpass the SNI quality standard. The conclusion of the research is the quality of the charcoal briquettes from the waste of biomass of coffee husk and coconut shell with tapioca flour recorder in the aspects of water content and ash content is still below the international quality standard and INS, but in the aspect of the heat value of the charcoal briquette the research results are above the SNI quality standard.